Pengaruh Gaya Kepemimpinan, Budaya Organisasi dan Disiplin terhadap Motivasi Serta Dampaknya pada Kinerja Pegawai di Badan Pengembangan Sumber Daya Manusia Provinsi Jambi - Firdaus, Firdaus; Bukit, Pantun; Yamali, Fakhrul Rozi (J-MAS (Jurnal Manajemen dan Sains), 2024)
The purpose of this study is to describe leadership style, organizational culture, discipline, motivation and employee performance at BPSDM Jambi Province and to analyze the influence of leadership style, organizational culture and work discipline partially and simultaneously directly and indirectly on work motivation and employee performance, as well as to analyze work motivation on employee performance. To answer the purpose of this research, this research is supported by theoretical studies related to research variables, namely leadership style, organizational culture, discipline, motivation and performance. In addition, the author is also looking for relevant previous research in the form of articles/journals and previous theses to support this research. The population in this study is employees of BPSDM Jambi Province, totaling 89 employees with conditions in 2022. The data analysis technique used in this study is through path analysis followed by hypothesis testing through F test (Simultaneous) and t test (Partial). From the path analysis test conducted, it was found that leadership style, organizational culture and discipline influenced Keria motivation by 75.7% while the rest was influenced by other variants. Leadership style, organizational culture and discipline affect 82.8% of employee performance in BPSDM Jambi Province. This study concludes leadership style, organizational culture, discipline, motivation and employee performance in good and high condition. In addition, leadership style, organizational culture and work discipline partially and simultaneously have a positive and significant influence on employee motivation and performance at BPSDM Jambi Province. Similarly, work motivation has a positive and significant influence on employee performance.